Benefits of controlled-release fertilizers for potato sustainable nitrogen management - Xue, Huiling; Zheng, Xiaofan; Wei, Hong; Yang, Jing; Alva, Ashok; Fan, Mingshou; Zhang, Ziyi (Frontiers in Environmental Science, 2024)
The evaluation of potato response to controlled-release fertilizers (CRFs), as a sole source of nitrogen (N) or as a blend with a soluble N source, is essential to 1) develop the best management recommendations for using CRFs in potato production and 2) provide guidelines to CRF manufacturers for developing an optimal product. This study aimed to evaluate the potato yield and quality responses to N CRFs (polymer-coated urea [PCU]) vs soluble N sources. The experiments were conducted in major potato-growing regions in the United States and China. The current industry-recommended practice of 112 kg N/ha pre-plant soil broadcast of urea plus five in-season fertigations of 224 kg N/ha as urea ammonium nitrate (UAN-32) was compared to a single pre-plant application of 224 kg N/ha as a CRF as the sole source of N or as multiple blends of CRFs and soluble N sources (i.e., urea) at various ratios. The results demonstrated that petiole nitrate_N (NO3_N) levels and tuber yield with single pre-plant broadcast applications of 224 kg N/ha as CRF/urea blends (ratio of 25/75 or 50/50) were similar to those obtained with industry-standard N management practice. N uptake and yield were significantly greater with 220 kg/ha N as the CRF than those with the same N rate as urea. Unlike the current potato industry N practice, using CRFs as either a sole source of N or blended with urea reduces the total N rate and application frequency.